Phagocytic Activity and Monocyte Chemotactic Protein Expression by Pulmonary Macrophages in Persistent Pulmonary Cryptococcosis - He, Wu (American Society for Microbiology, 2003)
The mechanisms by which Cryptococcus neoformans persists in an immunocompetent host are not well understood. Using a rat model of persistent infection, we investigated the ability of pulmonary macrophages (PuM) to phagocytize C. neoformans and produce monocyte chemotactic protein 1 (MCP-1) as a function of the length of time of infection and opsonin. The ability of macrophages to affect serum-mediated phagocytosis varied over the course of infection and was dependent on CD11b/c and CD18 expression. Infection resulted in increased MCP-1 levels within the lung, though the actual amounts varied over the course of infection. Immunohistochemical studies localized MCP-1 expression to macrophages and epithelioid cells. Enhanced production of MCP-1 by PuM from infected rats was confirmed by ex vivo studies. Induction of MCP-1 following serum-mediated phagocytosis was observed for PuM from both infected and noninfected rats and depended on the interaction of C. neoformans with CD11b/c and CD18. Specific antibody was more efficient than serum in promoting phagocytosis and consistently elicited more MCP-1. The relative amount of MCP-1 produced in association with phagocytosis was similar for PuM at all lengths of time of infection. Decreased MCP-1 production was observed for PuM obtained from older rats, including long-term (8 to 10 months)-infected and age-matched controls, suggesting that aging may affect the production of MCP-1 by PuM in response to cryptococcal infection. In summary, our results show that macrophages are an important source of MCP-1 during pulmonary cryptococcosis and that MCP-1 production is actively regulated during infection. Furthermore, we find that phagocytosis of C. neoformans can serve as an important stimulus for MCP-1 production by PuM, though the efficiency of this process is dependent on the opsonin type and may be affected by aging.